Factors Affecting the Performance of the Mutual Fund in Nepal (The Lumbini Journal of Business and Economics, 2023)
This study examines macro and micro factors affecting Nepalese mutual fund results. This study used panel data from March 2016 to November 2022 to determine the success factors of Nepal's 16 mutual funds.Nepalese mutual funds' irregular performance is due to national economic conditions and individual fund peculiarities. This research analyzes the influence of economic events and fund attributes on the performance of Nepalese mutual funds by using risk-adjusted returns proposed by William Sharpe (1994). This research evaluated how macroeconomic and fund-factor changes affected Nepal's mutual funds.The results show a positive relationship between fund age, assets turnover ratio, fund size, and exchange rate. Liquidity is a non-factor in mutual fund performance, but growth in gross domestic product, inflation, interest rates, and the money supply (M2) all harm fund return. Managers of mutual funds are encouraged to follow the recommendations made in this study to keep their portfolios as diversified as possible.